Finite element analysis of circumferential crack behavior in cement-femoral prosthesis interface - Oshkour, A.A.; Davoodi, M.M.; Abu Osman, Noor Azuan; Yau, Y.H.; Tarlochan, F.; Wan Abas, Wan Abu Bakar (Elsevier, 2013)
Investigating the crack behavior in the cement mantle can improve total hip replacement performance by lessening the effects of crack failure and femoral prosthesis loosening. This study analyzed the behavior of the internal circumferential cracks located in the cement layer of the cement-prosthesis interface during the main phases of the gait cycle. The extended finite element method was used in determining the stress intensity factors to identify the crack behavior. An adverse relationship was found between the stress intensity factors and the distance from the distal end. Consequently, the maximum stress intensity factors were observed at the distal part, specifically at the corner of the cement mantle. Additionally, the highest values of K-I, K-II, and K-III were presented during the single leg stance and push off phases, whereas the swing phase showed the minimum stress intensity factors. In addition, K-I and K-III were identified to be the dominant stress intensity factors and were respectively enhanced along the proximal to the distal end by about 89.5 and 65.9 in the lateral side and 63.7 and 56.5 in the medial side. This finding indicates higher risks of cement mantle fracture and fatigue crack propagation at the distal area.